Illegal Logging Di Kalimantan Selatan (Studi di Taman Hutan Raya Sultan Adam Kalimantan Selatan): Illegal Logging in South Kalimantan (Study in The Grand Forest Park of Sultan Adam of South Kalimantan) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
Abstract: This study of concerning phenomenon of illegal logging is conducted at society community doing activity of illegal logging in the Grand Forest Park of Sultan Adam, a conservation area in South Kalimantan which at one blow function as catchment area of the Dam of Riarn Kanan. This dam is sharing very vital for society of South Kalimantan that is beside as electric power supply, also as source of raw material drinking water, irrigation of agriculture and fishery, flood control, and others which its taking place is influenced by looking after of the Grand Forest Park of Sultan Adam as its catchment area. This study is to know the cause factors and process the happening of illegal logging in local level so that can determine the related solution alternative with the the problems. The primary data in this study were collected by using principle of theoretical sampling and principal of snow ball of passing process interview that assumed know the phenomenon of illegal logging. They are farmer, worker in wood sector, consisted of the operator of chainsaw and truck chauffeur, sawmill owner, NGO, as well as related government agency with the forestry business. Beside that is also supported by data skunder publicized by a related governmental institution. Method used in this study is descriptive qualitative intended to study the data or fact is later on interpreted in such a manner so that result of analysis can give the illustration of concerning process and cause factors of the happening of illegal logging in the Grand Forest Park of Sultan Adam. Result of this study indicates that the process of the happening of illegal logging in the Grand Forest Park of Sultan Adam entangle governmental agency, capital owner (boss) and from society circle conducted by various modus operandi to interrogate from punish lassoing and strive smoothly its activity. This modus operandi is conducted by partys in concerned in activity of illegal logging of either through direct and also indirectly as according to ability and authority of each consisted of the related modus operandi with the legality of wood, transportation of wood, community of effort, reason and wood usage. While factors causing the happening of illegal logging is related and explainable with a few aspect, that is legality aspect, social economics of society, difference of wood supply and demand and also rule of law enforcement.